Passive Smoking and Impaired Endothelium-Dependent Arterial Dilatation in Healthy Young Adults - David S. Celermajer; Mark Adams; Peter Clarkson; J. Robinson; Robyn J. McCredie; Ann E. Donald; John Deanfield (1996)
Passive smoking has been linked to an increased risk of dying from atherosclerotic heart disease. Since endothelial dysfunction is an early feature of atherogenesis and occurs in young adults who actively smoke cigarettes, we hypothesized that passive smoking might also be associated with endothelial damage in healthy young-adult nonsmokers.